Novos registros de Pseudosuchia para o Triássico sul brasileiro e suas implicações - Oliveira, Letícia Rezende de (2023)
The diversity of Archosauria preserved in the Triassic of Rio Grande do Sul has increased every year, either with the discovery of new materials of already known species or with the impact of new species. Both contribute to the understanding of the Triassic fauna with new inferences about its distribution, paleoecology, and intra- and interspecific relationships. In this work, two new pseudosuchian materials are described for the Santa Maria Supersequence. The first part of the work presents isolated materials from a large Loricata, with the elementsin excellent condition, collected at the Linha Várzea fossil site in the city of Paraíso do Sul, Dinodontosaurus Assemblage Zone. Corroborating t the conclusions of the anatomical comparisons, phylogenetic support was achived to assign part of the material to the genus Prestosuchus, which gives importance to the specimens by adding anatomical data on elements with low sampling (such as the ilium) and reinforcing the large dimensions reached by the species. Still, the work adds to the Triassic scenario a new outcrop with records for the group, increasing knowledge about the distribution of Prestosuchus during the Mesotriassic. The second part of the work describes materials composed of skull, partial axial skeleton and partial dorsal armor that were found in the fossiliferous site Pivetta in the city of Restinga Seca, Hyperodapedon Assemblage Zone, Late Triassic. The type material is associated but slightly dsartculated. Anatomical comparison and phylogenetic analysis allowed the identification of the material as a non-aetosaur Aetosauriformes not registered so far, with unique characteristics such as the presence of square osteoderms with two spikes. The new species increases the phylogenetic support among the Aetosauriformes, a recently reclassified group with few representatives, and stands out in the world context, being the oldest record of the clade and the first for Gondwana.